GIS-material for the archaeological project: Ditch and electric cable by two stone settings, RAÄ 78:1 and 2 - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned laying of an electric cable and trenching for a new ditch, a limited area by the roadside just north of the stone settings RAÄ 78:1 and 2 in Borg parish, Norrköping municipality, was investigated. It was established that the archaeological site did not extend to the affected roadside and no further archaeological measures were thus suggested.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the preliminary investigation was to delimit the protected area of the stone settings RAÄ 78:1 and 2. If any other archaeological remains were found, the aim was to excavate and document these before the cable laying could continue.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Under en halv dag undersöktes ett begränsat område invid vägkant strax norr om stensättningarna RAÄ 78:1 och 2 i Borgs socken, Norrköpings kommun. Anledningen var planer på att gräva ned en elkabel samt att anlägga ett dike längs med vägen. Det kunde konstateras att fornlämningen inte sträckte sig ner till det berörda arbetsområdet varför ingen vidare arkeologisk åtgärd föreslås.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökning var att begränsa fornlämningsområdet till stensättningarna RAÄ 78:1 och 2. Om fornlämning påträffades skulle denna undersökas och dokumenteras innan anläggningsarbetena kunde fortskrida.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Dike och elkabel invid två stensättningar, RAÄ 78:1 och 2
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi